2021 IEEE Symposium Series on Computational Intelligence (SSCI) 2021
DOI: 10.1109/ssci50451.2021.9659983
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Networks for Railway Switch Detection and Classification Using Onboard Camera Images

Abstract: Recent years have seen major advances in Artificial Intelligence (AI) methods for environment perception in intelligent transportation systems. Although most of them have been achieved in the automotive sector there is a similar demand in the railway domain. This paper investigates Deep Neural Network (DNN) based environment perception using vehicle-borne camera images from the rail domain. Specifically, railway switch detection and classification are addressed as a relevant example for a DNN application with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The CNN is mainly designed for image data [ 81 , 82 , 83 ], and the RNN is widely used to analyse time series and sequence data [ 23 , 84 ]. The DNN can be used for track component classification [ 85 ], railway defect detection [ 86 ], and track settlement prediction [ 87 ]. The ANN is commonly used for engineering to explore the importance of input features to output parameters.…”
Section: Prediction Methods Based On Machine Learningmentioning
confidence: 99%
“…The CNN is mainly designed for image data [ 81 , 82 , 83 ], and the RNN is widely used to analyse time series and sequence data [ 23 , 84 ]. The DNN can be used for track component classification [ 85 ], railway defect detection [ 86 ], and track settlement prediction [ 87 ]. The ANN is commonly used for engineering to explore the importance of input features to output parameters.…”
Section: Prediction Methods Based On Machine Learningmentioning
confidence: 99%
“…In another study, accurate estimation of recoverable train delay can assist railway dispatchers in rescheduling trains and improving service reliability [21]. The researchers aimed to develop a model for predicting primary delay recovery (PDR) based on operational data from the Wuhan-Guangzhou (W-G) high-speed railway.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Although the model's foundation was built using W-G HSR data, it could be easily extended to other HSR systems. The proposed approach could benefit professionals and academics interested in disruption management [21].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…DNN models can also be used for track component classification, e.g. railway switch type classification [45]. In addition, Shibao and Jie [46] applied the DNN model to landslide susceptibility mapping of the Sichuan-Tibet Railway and found that the DNN model can provide an accuracy of 84% in both the training and testing process.…”
Section: Introductionmentioning
confidence: 99%